Challenging the Rule of Law in the East African Court of Justice - Kisakye, Diana (2021)
Even though Africa has proven to be the most fertile ground for testing international legal regimes, scholarly accounts remain pessimistic in assessing these experiments. Drawing on international adjudication theories, scholars paint a gloomy picture of Africa’s Regional Economic Community (REC) courts, dubbing them as having limited or narrow authority (Alter, Helfer and Madsen 2016). By favouring state-driven compliance processes as a measure of performance, these approaches understate the peculiarities in which REC courts operate. Located at the intersection of opposing and fragile national and regional integration politics, the courts rely on key non-state actors to foster judicial empowerment (Gathii 2020). Likewise, courts in hybrid democracies in Africa count on allies to construct judicial autonomy (Trochev and Ellett 2014). Even though recent work on African REC courts posits that international adjudication in Africa is carving out its own path, a systematic analysis of how these courts negotiate judicial politics is still lacking. Through an in-depth study of the East African Court of Justice (EACJ), this paper seeks to examine how Africa’s REC courts construct and exercise their power. It highlights the promising and volatile path that these courts have trodden and seeks to explain their emerging judicial power. Following Piana (2020), I conceptualise judicial power as a combination of the actors’ agency and the structural conditions conferring authority to the court. Thus, the paper foregrounds judges and their key constituencies as a window into understanding the adjudication processes. Arguing that judges are social and political actors, who operate within existing power configurations, the paper considers the judges’ diverse relational attributes as central to shaping judicial power. The author draws on expert interviews, court documents and an analysis of judgements to systematically assess the courts’ functioning and interrogate the relevant actors’ intrinsic motivations. Initially, the paper delves into a review of the court’s structural norms (organisational and institutional). Subsequently, it provides insights into the court’s composition and output and ponders what these attributes could reveal about the performance of international courts in Africa. Lastly, it briefly considers international adjudication theories and illustrates that they do not transfer with ease to the EACJ. This paper finds that the EACJ has gone from having an empty docket to becoming an active court that proactively interprets Treaty provisions to an impressive range of subject matters. Likewise, preliminary findings from interviews highlight the use of the courts as arenas of political mobilisation. However, the opaque procedure for judges’ nomination poses an obstacle to judicial independence and the courts’ legitimacy. In sum, the paper highlights that REC courts in Africa are challenging international adjudication theories by pushing their expectations and breaking new ground. It also expands our understanding of some of the key players in regional politics whilst unravelling intricate details about the rule of law in Africa.
Keywords: The rule of law; East African Court of Justice